Survival during Renal Replacement Therapy among African Americans Infected with HIV Type 1 in Urban Baltimore, Maryland - Atta, Mohamed G. (2007)
BACKGROUND: African Americans with human immunodeficiency virus type 1 (HIV-1) infection and kidney disease are at increased risk of end-stage renal disease requiring renal replacement therapy (RRT), particularly in urban areas with high rates of poverty and injection drug use. It is unknown how the widespread use of highly active antiretroviral therapy (HAART) has affected survival during RRT in this vulnerable population. METHODS: African American patients infected with HIV-1 who required RRT were identified from 2 cohorts that included 4509 Africans Americans infected with HIV-1 who were recruited during the period 1988–2004 in Baltimore, Maryland. Survival after initiation of RRT was compared for those who initiated treatment in the pre-HAART and the HAART eras using Kaplan-Meier curves. Cox proportional hazards regression analysis was used to adjust for potential confounders. RESULTS: RRT was initiated in 162 patients (3.6%) during 10.6 years of follow-up (119 during the HAART era). Compared with patients who started RRT in the pre-HAART era, those in the HAART era were older (P< .001) and more likely to have CD4 cell counts of ≥200 cells/mm(3) (P = .01). A total of 126 patients (78%) died during follow-up; among those who initiated RRT during the HAART era, 87 deaths occurred (73%). Median survival time in the pre-HAART era was 22.4 months (95% confidence interval [CI], 9.3–30.7); during the HAART era, it was 19.9 months (95% CI, 14.7–26.5; P = .94). In the multiple Cox regression model, factors independently associated with increased mortality included age (hazard ratio [HR], 1.30; 95% CI, 1.06–1.60; P = .01), lower serum albumin level (HR, 0.72; 95% CI, 0.57–0.91; P< .007), lower CD4 cell count (HR, 0.90; 95% CI, 0.82–0.99; P< .03), and the lack of HAART (HR, 0.52; 95% CI, 0.33–0.82; P = .005). CONCLUSIONS: Older age, lower serum albumin level, lower CD4 cell count, and the lack of HAART are independent predictors of poor survival among African Americans infected with HIV-1 undergoing RRT in a resource-limited urban area. RRT survival was similar in the pre-HAART and HAART eras, likely reflecting inadequate HIV treatment in this population.